Transitional and turbulent flow of non-Newtonian slurries in pipes - Slatter, Paul Thomas (Department of Civil Engineering, 2016)
The only reliable approach open to designers of pipeline systems conveying non-Newtonian slurries in the turbulent flow regime has been large scale-pipe-tests. This thesis addresses this design problem, with particular emphasis on the theoretical modelling of the laminar/turbulent transition and turbulent flow behaviour of these slurries in pipes. The literature and theory pertinent to-the flow of slurries in pipes-is examined. The development of non-Newtonian Reynolds numbers and laminar/turbulent transition criteria are presented and existing theoretical models for predicting turbulent flow are reviewed. Three test facilities were built for the establishment of a data base of non-Newtonian slurry behaviour - a tube viscometer and two pumped recirculating pipe test rigs.